Phytochemical composition in hexane and methanolic leaf extract of Vernonia amygdalina - Siti Fairuz Y.,; Ismail S.I.,; Farah Farhanah H.,; Mahmud T.M.M., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Vernonia amygdalina or known as Pokok Bismillah in Malaysia is commonly used for medicinal purposes due to their pharmacological effects. The present study aimed to identify the chemical composition by GC-MS analysis of hexane and methanolic crude extract of V. amygdalina. Thirty-two and twenty-two components were identified from their fragmentation pattern in hexane and methanolic extract, respectively. Major components in hexane extract dominated by tetrapentacontane (21.56%), nonacosane (13.06%), squalene (12.77%), phytol (8.73%), δ-7,25-stigmastadienol (7.20%) and α-tocopherol (5.18%). Meanwhile, methanolic extract were linolenic acid (21.94%), hexadecanoic acid (15.51%), 2,3-hexanedione (12.40%), linoleic acid (10.45%), phytol (8.81%) and decanamide (5.92%). These compounds could be useful for biomedical activities and as a therapeutic agent.